Recent Advances in Enhancement Strategies for Osteogenic Differentiation of Mesenchymal Stem Cells in Bone Tissue Engineering - Zha, Kangkang; Tian, Yue; Panayi, Adriana C.; Mi, Bobin; Liu, Guohui (Frontiers in Cell and Developmental Biology, 2022)
Although bone is an organ that displays potential for self-healing after damage, bone regeneration does not occur properly in some instances and it is still a challenge to treat large bone defect. The development of bone tissue engineering provides a new approach for treatment of bone defect. Among various cell types, mesenchymal stem cell (MSC) represents one of the most promising seed cells in bone tissue engineering due to its functions of osteogenic differentiation, immunomodulation, and secretion of cytokines. Regulation of osteogenic differentiation of MSCs has become an area of extensive research over the past few years. This review provides an overview of recent research progress in enhancement strategies for MSC osteogenesis, including improvement of methods in cell type selection, culture condition, biophysical stimulation, crosstalk with macrophage and scaffold. It is favorable for further understanding of MSC osteogenesis and development of MSC-based bone tissue engineering.